Adamantyl Analogues of Paracetamol as Potent Analgesic Drugs via Inhibition of TRPA1 - Fresno, Nieves; Pérez-Fernández, Ruth; Goicoechea, Carlos; Alkorta, Ibon; Fernández-Carvajal, Asia; de la Torre-Martínez, Roberto; Quirce, Susana; Ferrer-Montiel, Antonio; Martín, M. Isabel; Goya, Pilar; Elguero, José (PLOS ONE, 2014)
Paracetamol also known as acetaminophen, is a widely used analgesic and antipyretic agent. We report the synthesis and biological evaluation of adamantyl analogues of paracetamol with important analgesic properties. The mechanism of nociception of compound 6a/b, an analog of paracetamol, is not exerted through direct interaction with cannabinoid receptors, nor by inhibiting COX. It behaves as an interesting selective TRPA1 channel antagonist, which may be responsible for its analgesic properties, whereas it has no effect on the TRPM8 nor TRPV1 channels. The possibility of replacing a phenyl ring by an adamantyl ring opens new avenues in other fields of medicinal chemistry.